Адаптационный дискурс как средство маргинализации рабочего класса в постсоветских обществах - Рябчук, А. (Социология: теория, методы, маркетинг, 2007)
The article explores the role of "adaptation discourse" in the creation and reproduction of class inequalities in post-communist societies. Within this discourse it is argued that the extent to which a particular individual has successfully "adapted" to the new socio-economic conditions, determines his or her current position in society. However,the main drawbacks of this discourse are that it views "adaptation potential" in purely individualized terms, neglecting any structural factors that allow somebody to adapt better than others; that possession of this adaptation potential in itself becomes a distinguishing factor in creation and reproduction of inequalities; and finally, that the need to adapt to the market economy is presented as normative and self-evident,therefore preventing any critical reassessment of the current situation.